2003
DOI: 10.1242/jeb.00237
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of foregut synaptic activity controls resorption of molting fluid during larval molts of the mothManduca sexta

Abstract: The regulation and organization of a variety of stereotyped behaviors are essential for many aspects of animal development. One such collection is a series of ecdysial-related motor programs that lead to the shedding of an insect's old cuticle during a molt. Like all insects, the growth of larval Manduca sexta moths is limited by its inelastic cuticle. Consequently, growing larvae undergo a series of molts in which the old cuticle is shed and replaced by a new, larger cuticle. The two ecdysial-related motor pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(28 citation statements)
references
References 43 publications
1
27
0
Order By: Relevance
“…Recently, we found that the proper modulation of anterior foregut motility is essential for the successful completion of a larval-larval molt of M. sexta (Bestman and Booker, 2003). As described by Miles and Booker (Miles and Booker, 1994) the anterior foregut of M. sexta larvae is composed of a muscular section comprising the buccal cavity, the pharynx, esophagus, and the crop.…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations
“…Recently, we found that the proper modulation of anterior foregut motility is essential for the successful completion of a larval-larval molt of M. sexta (Bestman and Booker, 2003). As described by Miles and Booker (Miles and Booker, 1994) the anterior foregut of M. sexta larvae is composed of a muscular section comprising the buccal cavity, the pharynx, esophagus, and the crop.…”
Section: Introductionmentioning
confidence: 95%
“…To gain access to M. sexta anterior foregut musculature and nervous system, larvae were dissected along the dorsal midline and the anterior foregut, brain and frontal ganglion were surgically isolated according to methods described (Bestman and Booker, 2003). The 'semi-intact' anterior foregut preparations prepared in this manner were transferred and pinned to a 35·mm plastic tissue culture dish lined with silicone elastomer (Sylgard; Dow Corning, Midland, MI, USA).…”
Section: Anterior Foregut Preparation and Recording Techniquesmentioning
confidence: 99%
See 2 more Smart Citations
“…This precedes the critical phase of air swallowing. Hence, the crop initially fills with moulting fluid then air (Miles and Booker, 1998;Bestman and Booker, 2003). Fluid swallowing of a different nature may also be assumed to take part in the moulting of some aquatic insects (in this case substituting for air-swallowing behaviour).…”
Section: The Role Of the Insect Fg In Moulting-related Behaviourmentioning
confidence: 99%